Seismic Behavior of Nonductile RC Frame Slotted with Corrugated Steel Plate Shear Walls - Ningning Feng; Changsheng Wu (Advances in Civil Engineering)
Two specimens of nonductile reinforced concrete (RC) frame (ND-1) and nonductile RC frame retrofitted by corrugated steel plate shear walls slotted with columns (ND-2) are established by finite element. These specimens have same dimensions and steel skeletons. Finite element models had been verified by the existing experimental results. The hysteresis curves, skeleton curves, ductility, and stiffness curves of Specimen ND-1 and Specimen ND-2 are compared. The results show that the reinforcement effect is significant. Twenty-four models are built to study the seismic behavior on different influence parameters. The parameters are slit width, thickness of corrugated steel plate shear walls, concrete strength of nonductile RC frame, and boundary conditions of corrugated steel plate shear walls at slotted parts. The results indicate that the strength is declined with the increase of slit width. With the increase of thickness and concrete strength, the strength and stiffness are enhanced. The strength is larger with the boundary than without. Slit width and thickness have an important impact on the stiffness. Concrete strength and boundary conditions have little impact on stiffness. The strengthened nonductile RC frames have enough ductility.